THE INFLUENCE OF PERCEPTION, CONSUMER AWARENESS AND PREFERENCES ON CONSUMER BEHAVIOR IN CONSUMING LOCAL FRUIT IN MAJOR CITIES IN INDONESIA - Syarifuddin Syarifuddin; Sofyan Oktavian Tubagus; Anita Bawaiqki Wandanaya; Febri Sari Siahaan; Ilham Arief (Sean Institute, 2023)
The aim of this research is to determine the characteristics of respondents regarding consumer behavior when consuming local fruit. This research uses qualitative and quantitative analysis. Sampling was carried out randomly, with a total of 100 respondents. The data collection technique used in this research is a questionnaire. Statistical Product and Service Solution (SPSS). The data obtained will be processed and then analyzed using the multiple linear regression method. The results of the data analysis show consumer behavior can be explained by the independent variables used in the model, namely awareness, perception, and preference. Based on the results of the F test, it shows that the three independent variables observed have a significant effect together on the behavior of consuming local fruit. The t test results show that consumer awareness has a real positive effect on the dominant indicator of the consumer's physical condition after consuming local fruit, consumer perception has an insignificant positive effect on the dominant indicator, namely the consumer's time spent consuming local fruit and consumer preferences have a real positive effect on the dominant indicator, namely product attributes, where consumers find it easy to obtain local fruit on consumer behavior in consuming fruit.